Limited alignment of publicly competitive disease funding with disease burden in Japan - Nomura, Shuhei; Yoneoka, Daisuke; Tanaka, Shiori; Makuuchi, Ryoko; Sakamoto, Haruka; Ishizuka, Aya; Nakamura, Haruyo; Kubota, Anna; Shibuya, Kenji (PloS one, 2020)
OBJECTIVE: The need to align investments in health research and development (R&D) with public health needs is one of the most important public health challenges in Japan. We examined the alignment of disease-specific publicly competitive R&D funding to the disease burden in the country. METHODS: We analyzed publicly available data on competitive public funding for health in 2015 and 2016 and compared it to disability-adjusted life year (DALYs) in 2016, which were obtained from the Global Burden of Disease (GBD) 2017 study. Their alignment was assessed as a percentage distribution among 22 GBD disease groups. Funding was allocated to the 22 disease groups based on natural language processing, using textual information such as project title and abstract for each research project, while considering for the frequency of information. RESULTS: Total publicly competitive funding in health R&D in 2015 and 2016 reached 344.1 billion JPY (about 3.0 billion USD) for 32,204 awarded projects. About 49.5% of the funding was classifiable for disease-specific projects. Five GDB disease groups were significantly and relatively well-funded compared to their contributions to Japan's DALY, including neglected tropical diseases and malaria (funding vs DALY = 1.7% vs 0.0%, p<0.01) and neoplasms (28.5% vs 19.2%, p<0.001). In contrast, four GDB disease groups were significantly under-funded, including cardiovascular diseases (8.0% vs 14.8%, p<0.001) and musculoskeletal disorders (1.0% vs 11.9%, p<0.001). These percentages do not include unclassifiable funding. CONCLUSIONS: While caution is necessary as this study was not able to consider public in-house funding and the methodological uncertainties could not be ruled out, the analysis may provide a snapshot of the limited alignment between publicly competitive disease-specific funding and the disease burden in the country. The results call for greater management over the allocation of scarce resources on health R&D. DALYs will serve as a crucial, but not the only, consideration in aligning Japan's research priorities with the public health needs. In addition, the algorithms for natural language processing used in this study require continued efforts to improve accuracy.
Keywords: Research; investice; finanční podpora; Japan; mezinárodní klasifikace nemocí; Financing, Government; Biomedical Research; Disease; náklady na zdravotní péči; Quality-Adjusted Life Years; financování vládou; výzkum; globální zátěž nemocemi; ekonomické soutěžení; Investments; Global Burden of Disease; biomedicínský výzkum; lidé; Public Health; International Classification of Diseases; kvalitativně upravené roky života; Humans; Japonsko; veřejné zdravotnictví; Financial Support; Health Care Costs; nemoc; Economic Competition